2D/2D Heterostructures: Rational Design for Advanced Batteries and Electrocatalysis. Issue 1 (4th April 2021) - Mei, Jun; Liao, Ting; Sun, Ziqi
Abstract : Two‐dimensional/two‐dimensional (2D/2D) heterostructures consisting of two or more 2D building blocks possess intriguing electronic features at the nanosized interfacial regions, endowing the possibility for effectively modulating the confinement, and transport of charge carriers, excitons, photons, phonons, etc . to bring about a wide range of extraordinary physical, chemical, thermal, and/or mechanical properties. By rational design and synthesis of 2D/2D heterostructures, electrochemical properties for advanced batteries and electrocatalysis can be well regulated to meet some practical requirements. In this review, a summary on the commonly employed synthetic strategies for 2D/2D heterostructures is first given, followed by a comprehensive review on recent progress for their applications in batteries and various electrocatalysis reactions. Finally, a critical outlook on the current challenges and promising solutions is presented, which is expected to offer some insightful ideas on the design principles of advanced 2D‐based nanomaterials to address the current challenges in sustainable energy storages and green fuel generations. Abstract : 2D/2D heterostructures, consisting of two or more 2D basic building blocks that are synthesised by either exfoliation or chemical growth strategy, exhibit a variety of extraordinary physical, chemical, thermal and/or mechanical properties for promoting electrochemical performance, and are expected to be promising nanomaterials in advanced batteries and electrocatalysis fields.